Individual characters in the Czech comedies of second half of 19th century - Smrčka, Jiří (Bohemica Olomucensia, 2014)
The paper deals with displaying social details in the Czech comedies, especially the J. Štolba's and V. Štech's. These comedies are very important for understanding the development of Czech drama.